Penerapan Metode Even-Rodeh Code Pada Aplikasi Lirik Lagu Berbasis Android - Riska Devi Hanum; Henky Japina (Himpunan Dosen Gemilang Indonesia (HDGI), 2024)
Song lyrics in Android-based applications sometimes have repeated verses in each verse, therefore a compression application is needed so that they don't have a lot of lyrics. By applying the Even-Rodeh Code method, we can find out the performance of compressing song lyrics on Android, so that large song lyrics are compressed to a smaller size. This song lyrics application is an application that has a lot of text data. Because the song lyrics application stores various kinds of lyric texts from various existing songs, both regional songs, national songs, domestic and foreign songs. The factors that determine the algorithm selection are always used in data compression, namely (memory, PC speed), compression speed, compression result size, amount of redundancy and algorithm complexity. One of the known compression algorithms is the Even-Rodeh Code algorithm. The Even-Rodeh Code algorithm is a data compression algorithm that encodes characters based on the frequency of each character.